PENGARUH KUALITAS AKTIVA PRODUKTIF DAN NET PERFORMING FINANCING (NPF) TERHADAP NET OPERATING MARGIN (NOM) BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH PERIODE JUNI 2014 – MARET 2020 - Aris Munandar (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2020)
Net Operating Margin (NOM) is a ratio that is needed to improve the ability of banks to manage their entire productivity in order to produce a higher net. While Non-Performing Financing (NPF) is an indicator of credit risk (financing) of Islamic banks. Banks with high NPFs are less effective. Consider a bank with a lower NPF, more efficient. This study aims to look at the effect of Earning Asset Quality and Non-Performing Financing (NPF) on Net Operating Margin (NOM) in Sharia Commercial Banks and Sharia Business Units. The data used in this study is monthly coherent data from the period June 2014 to March 2020. Technical data analysis uses multiple regression models that are processed with IBM SPSS V.26.0. The results showed that the Earning Assets Quality (KAP) had a significant negative effect on the Net Operating Margin (NOM) variable with a KAP coefficient of -0.017 with a significance level of 0.610. Net Performing Financing (NPF) has a significant negative effect on the Net Operating Margin (NOM) variable with a NPF coefficient of - 0.482 with a significance level of 0,000. F test results (simultaneous) Earning Asset Quality (KAP) and Net Performing Financing (NPF) have a significant effect on the Net Operating Margin (NOM) of BUS and UUS. Test the coefficient of determination (Adjusted R Square) of 0.732 or of 73.2%. This shows that Earning Asset Quality (KAP) and Net Performance Financing (NPF) contributed 73.2% to Net Operating Margin (NOM). While the remaining 26.8% was placed by other variables outside this study.